Motherisk Update: Counseling psychiatric patients about drug exposures during pregnancy - Einarson, Adrienne (1998)
QUESTION: Several of my patients with psychiatric disorders are either planning to conceive or are already pregnant. I find it difficult to reassure them about the safety of taking medications during pregnancy. How do you deal with such situations at Motherisk? ANSWER: These patients should be counseled in an unambiguous and consistent manner. They can be referred to the Motherisk Program, or Motherisk can fax up-to-date information to their physicians.